GTLN của biểu thức $-x^{2}$ + 4x – 5

GTLN của biểu thức $-x^{2}$ + 4x – 5

2 bình luận về “GTLN của biểu thức $-x^{2}$ + 4x – 5”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
     Ta có: -x^2 +4x – 5
            <=> -(x^2 – 2.2.x + 4) -1
             <=> -(x-2)^2 -1
     Vì -(x-2)^2 <0$\forall$ x
      => -(x-2)^2 -1 <-1 $\forall$ x
      Dấu = xảy ra <=> x – 2 = 0 => x = 2
        Vậy Max B = -1 <=> x = 2

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    Có A= -x²+4x-5=-(x²-4x+5)
    =-(x²-2×2+2²-2²+5)
    =-[(x-2)²+1]
     Vì(x-2)²≥0
    →(x-2)²+1≥1
    →-[(x-2)²+1)≤1
    Hay A đạt gtln=1⇔x-2=0⇔x=2

    Trả lời

Viết một bình luận

Câu hỏi mới